2012
DOI: 10.1590/s1808-16572012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Frequência e fatores associados à infecção pelo vírus da diarreia viral bovina em bovinos leiteiros não vacinados no Estado do Maranhão

Abstract: RESUMOA frequência de anticorpos contra o vírus da diarreia viral bovina (BVDv) foi pesquisada na bacia leiteira do Estado do Maranhão. Amostras de soro sanguíneo de 920 fêmeas bovinas não vacinadas contra a diarreia viral bovina (bovine viral diarrhea, BVD) foram analisadas pelo método de ELISA indireto. O estudo foi realizado em 92 propriedades leiteiras, pertencentes a 23 municípios localizados nas regionais de Açailândia, Bacabal, Ilha de São Luís, Imperatriz e Pedreiras. As amostras de soro foram coletada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
4
0
3
Order By: Relevance
“…The high number of herds that had at least one reagent animal (100.0%) is similar to the results reported by Fino et al (2013) in the state of Santa Catarina and compatible with the 82.4% found in Rio Grande do Sul (QUINCOZES et al, 2007) and with the 97.6% found in the state of Maranhão (CHAVES et al, 2012). These results could be associated with inadequate procedures of sanitary management on the family farms in question, resulting in the introduction of viremic cattle (acute infection or PI).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The high number of herds that had at least one reagent animal (100.0%) is similar to the results reported by Fino et al (2013) in the state of Santa Catarina and compatible with the 82.4% found in Rio Grande do Sul (QUINCOZES et al, 2007) and with the 97.6% found in the state of Maranhão (CHAVES et al, 2012). These results could be associated with inadequate procedures of sanitary management on the family farms in question, resulting in the introduction of viremic cattle (acute infection or PI).…”
Section: Discussionsupporting
confidence: 87%
“…Quincozes et al (2007) observed that the presence of sheep in consortium breeding systems has been considered a risk factor for the presence of anti-BVDV antibodies. Meanwhile, Chaves et al (2012) reported that pig breeding is a statistically significant risk factor for BVDV seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these variables were previously described in other studies as important risk factors for infections affecting cattle. Among the aforementioned variables, one finds purchase of animals, presence of sheep/goats and pigs, diarrhea, miscarriage and pasture sharing (BEZERRA et al, 2012;CHAVES et al, 2012;OLIVEIRA et al, 2013;PRAZERES et al, 2014;CARVALHO et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…En las comunidades rurales del Pontal del Paranapanema (São Paulo, Brasil), Gaeta et al (2018) detectaron un 37,4% de terneros con serología positiva. Por último, la frecuencia de anticuerpos contra HVBo-1 fue similar a las encontradas en los estados brasileños de Espírito Santo (Santos et al, 2014) y Maranhão (Chaves et al, 2012) y mayores que la encontrada en los asentamientos en el estado de São Paulo (Gaeta et al, 2018) y en Rio Grande do Sul (Becker et al, 2015). El muestreo, la edad de los animales y las distintas pruebas diagnósticas empleadas pueden estar relacionadas con los diferentes resultados encontrados en otros estudios (Coutinho et al, 2009).…”
Section: Discussionunclassified